#TITLE_ALTERNATIVE# - MAKARIM (NIM : 12213024), FAUZAN
In terms of cost, developing a geothermal power generation will require roughly 40% of all cost spent on wells and field development. This leads to a challenge for well, so that it is more cost efficient. To answer it, one of its innovations is by reducing the diameter into small one or commonly known as deep slim hole which cost roughly 25% of a conventional well. However, this cost efficient hole has a main disadvantage. It is generally not suitable for commercial production. Thus, another standard hole must be built in order for well to be commercialized. This condition creates question whether drilling a deep slim hole is actually cost efficient in the long term or only in the beginning. This paper will evaluate the economic side of the well by diameter, presents the cost comparison of a single well in small, standard, and large diameter, either vertical or deviated. It is clarified that the increase of diameter, depth, and deviated well increase the cost spent on well. This paper will also simulate scenario using 5 small or standard diameter in 0-100% drilling success rate, offering the best choice of scenario. It is found that deep slim hole is cost efficient if used in exploration phase when drilling success rate is low, but at the certain point where drilling success rate high enough, standard well is the best choice. It is then investigated further by sensitivity test of depth, cost, and drilling success rate, producing simple concept to determine when deep slim hole should be used by using the cost of slim hole and standard hole ratio.